An evaluation of two methods of teaching prospective clerks to type business letters - Hershey, Edna-Jean, author; Hinderman, Roy Aaron, 1900-, advisor; Heilig, Herb, committee member; Marshall, Thomas O., committee member (Colorado State University. Libraries, 1945)
To view the abstract, please see the full text of the document.
Covers not scanned.
Zip file contains appendix originally bound with thesis, includes eight sections. A: booklet "You Can Do It" describing activities at Denver's Emily Griffith Opportunity School; B: list of 14 Denver business firms aiding the study; C: Table 81, summary of job information on beginning clerk-typists required in the Fall. of 1944 by 15 employers in Denver; D: correspondence with four business schools; Table 82, summary of current letter-writing mechanics and techniques followed by Denver Business firms; F: specimen of tests used in the experiment; G: unit of instruction prepared for the study; and H: bibliography.
Keywords: Emily Griffith Opportunity School (Denver, Colo.); Commercial correspondence -- Study and teaching; Typewriting -- Study and teaching